π-fused diazocines with controllable photoswitching properties as molecular tweezers - Yuan, Wei (2024)
Diazocines, a type of photoswitch molecules, are distinguished by their unique conformation and photochromic properties. Molecular engineering of diazocines, especially the π-extended ones, remains challenging due to limited synthetic methods. Here, we developed three π-fused diazocines (BAZO-1, BAZO-2, and BAZO-3) via Bischler-Napieralski cyclization. Their isomerizations (Z ⇆ E) were switchable under visible light sources (427 and 630 nm). The size of their π-extension exerted a significant influence on the isomerization process, whereby the biggest fourfold ring-closure diazocine (BAZO-3) showed the fastest conversion rate (Z → E). Notably, the half-life (t1/2) of the E isomer of BAZO-3 was 14.6 times higher than that of the twofold ring-closure BAZO-1. Thus, BAZO-3 acted as a molecular tweezer based on double N-embedded pyrene units, allowing it to bind to pyrene through supramolecular interactions. This work may pave the way for designing novel photoswitches with long half-lives and lightcontrolled properties.